Numerical Simulations of Chemical-Assisted Steam Flooding in Offshore Heavy Oil Reservoirs after Water Flooding - Wei Zheng; Tingen Fan; Xianhong Tan; Weidong Jiang; Taichao Wang; Haojun Xie (Geofluids)
Chemical-assisted steam flooding (CASF) is a promising method for heavy oils. However, few researches have investigated the CASF performance on offshore heavy oil reservoirs recovery after water flooding. In this study, a numerical simulation model was developed to simulate CASF processes for offshore heavy oil reservoirs after water flooding. Then, a comparison of CASF and various thermal methods was made to assess the feasibility of CASF in an offshore heavy reservoir of Bohai Bay, China. Finally, sensitivity analysis was performed to evaluate the effects of the gas-liquid ratio, foaming agent concentration, surfactant concentration, the size of nitrogen foam slug, the size of surfactant slug, and the number of chemical injection round on CASF performance by the developed model. The results showed that the developed numerical method can precisely simulate the CASF processes. CASF is a potential and effective method for offshore heavy oil reservoirs after water flooding. The most suitable gas-liquid ratio was around 2 : 1 under the simulation conditions. Considering the economic benefit, it is significant to optimize the CASF parameters, such as foaming agent concentration, the size of nitrogen foam slug, and the number of chemical injection round.